2017
DOI: 10.3390/molecules22112006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Major Flavone C-Glycosides and Their Optimized Extraction from Cymbidium kanran Using Deep Eutectic Solvents

Abstract: Cymbidium kanran, an orchid exclusively distributed in Northeast Asia, has been highly valued as a decorative plant and traditional herbal medicine. Here, C. kanran extracts were prepared in 70% aqueous methanol using ultrasound-assisted extraction (UAE) and subjected to liquid chromatography-photodiode array detection and ultra-high performance liquid chromatography-quadrupole-time-of-flight-mass spectrometry analysis, which were used for quantitative and qualitative analysis, respectively. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…This level lies between 75 and 80% (w/v) found for polyphenol extraction with DES from M. oleifera leaves [23,34], and 78 and 80% (w/v) from olive leaves [21,35]. Other investigations reported 80% (w/w) for tartary buckwheat hull [36], 80% (w/w) for sea buckthorn leaves [37], 74% (w/w) for Cymbidium kanran [38] and 76.2% (w/w) for grape skin [39]. In all these optimization studies, the appropriate adjustment of water amount was shown to be critical for the extraction efficiency, because the DES/water proportion regulates features such as viscosity and polarity [40], which profoundly affect solute solubility, hence extraction performance.…”
Section: Extraction Process Optimizationmentioning
confidence: 86%
“…This level lies between 75 and 80% (w/v) found for polyphenol extraction with DES from M. oleifera leaves [23,34], and 78 and 80% (w/v) from olive leaves [21,35]. Other investigations reported 80% (w/w) for tartary buckwheat hull [36], 80% (w/w) for sea buckthorn leaves [37], 74% (w/w) for Cymbidium kanran [38] and 76.2% (w/w) for grape skin [39]. In all these optimization studies, the appropriate adjustment of water amount was shown to be critical for the extraction efficiency, because the DES/water proportion regulates features such as viscosity and polarity [40], which profoundly affect solute solubility, hence extraction performance.…”
Section: Extraction Process Optimizationmentioning
confidence: 86%
“…Yoo et al 43 used ChCl/1,6-hexanediol 1:7 molar with 32.5 wt % of water to extract phenolic compounds from coffee beans, where the best process conditions were an extraction temperature of 60 °C for 10 min assisted by ultrasound. In another work, Jeong et al 59 optimized the extraction of Cglycosylated flavones from Cymbidium kanran. For instance, Cui et al 60 optimize the extraction of genistin, genistein, and apigenin from pigeon pea roots.…”
Section: Optimization Of the Extraction Of Tfc L7o-g And Q3o-r By Cen...mentioning
confidence: 99%
“…Duplicate solvents were deleted. In this screening, 178 pairs of DESs 48,[86][87][88][89][90][91][92][93][94][95] and 143 commercially avialable IL pairs 96,97 were added to the search space, leading to a total of 8011 molecules defining the solvent search space. A complete list of screened solvents can be found in the ESI † .…”
Section: Solvent Screening Approach 321 Databasementioning
confidence: 99%